Genetic diversity of local corn (Zea mays) cultivars from South Amarasi, Kupang District, Indonesia by Inter Simple Sequence Repeats marker - Uslan Uslan; NUR JANNAH (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Uslan, Jannah N. 2020. Genetic diversity of local corn (Zea mays) cultivars from South Amarasi, Kupang District, Indonesia by Inter Simple Sequence Repeats marker. Biodiversitas 21: 1208-1214. Corn (Zea mays L.) is one of the most important food crops in Indonesia. However, the studies described their genetic variation is relatively poor. Therefore, the aim of this study was to analyze the genetic diversity of local corn cultivars from South Amarasi, Kupang District, East Nusa Tenggara (NTT), Indonesia using ISSR markers. The sampling was conducted in 4 different sites in Sub-district of Amarasi, Kupang District. A total of 11 corn cultivars from Sub-district of South Amarasi was collected. DNA isolation was performed by using CTAB Method. Clustering analysis was conducted on MSVP 3.2 software. It was shown that all ISSR-primers used (UBC 811, UBC 814 and UBC 824) were successfully produced polymorphic bands and represents the high genetic diversity of the local corn cultivars. The genetic distance index indicated that several corn cultivars from two different populations were geographically unclustered, although there are samples from several populations that have a low genetic distance. The genetic variation index also showed high genetic diversity among the populations. Further research on the exhaustive sample collection was needed to give an insight into the genetic diversity of local corn cultivars (Zea mays L.) from South Amarasi, Indonesia. Please write implementation of this research